Chemical reactions in electric pulse dispersion of iron in aqueous solutions; Russian Journal of Applied Chemistry; Vol. 81, iss. 5 - Danilenko N. B. Nina Borisovna; Savel'ev G. G.; Yavorovsky N. A. Nikolay Aleksandrovich; Yurmazova T. A. Tatyana Aleksandrovna (2008, 2008)
Title screen